English reading literacy of Malaysian lower secondary students using Rasch measurement model - Badrasawi, Kamal Jamil Ibrahim (Institute of Education, International Islamic University Malaysia, 2012)
English is an important second language in Malaysia. It is a compulsory school subject taught to all children in the national primary and secondary schools, to be used in their personal studies and future workplace/life. Given the importance of English, the development of English literacy needs to be monitored over time. However, this is currently done based on their results in national standardized examinations. The input from these national examinations, though useful, is insufficient to give a complete picture about the level of students' performance in English literacy as there are no national benchmarks at the different levels of schooling. This limitation is especially critical for students in the lower secondary stage as this level of schooling is considered as the foundation level in which the development of English literacy is necessary for their performance in the future at the upper levels of schooling, tertiary education, and their future career. Thus, this study seeks to examine the performance of these school children and attempts to answer questions related to their performance in this skill. Among them are these two major questions: What is the performance level of Malaysian lower secondary school children in English reading literacy? And which groups of Malaysian lower secondary school children are at risk of underachieving in English reading literacy? A sample of 944 Form 1, 2, and 3 students was selected from 11 national-type schools in two states in Malaysia using the multistage cluster random sampling procedure. A test of English reading, comprising 60 items, was used. Both RMM and MFRM analyses, in addition to descriptive analyses, were used to answer the research questions. The results indicated that, in general, male students slightly outperformed female students, and Form 1 and 2 students outperformed Form 3 students. Closer examination of other demographic variables including race, school location, parents' education and SES indicated that gender does not exclusively influence student performance. The results also showed that items within the same reading skill categories did not have the same difficulty level. The most difficult skill category was interpreting information and the easiest one was finding out word meanings. To conclude, not all males performed better and not all females were underachieving. The findings show a need for monitoring of students' progress over time and the use of a robust measurement model to do so. Furthermore, the use of the Rasch Measurement Model for test equating and in item analysis demonstrates the robustness and utility of the model in ensuring fair measurement. Implications and recommendations are stated for stakeholders.